1992
DOI: 10.1111/j.1442-9071.1992.tb00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of congenital dacryocystocoele

Abstract: Congenital dacryocystocoele occurs when the nasolacrimal drainage apparatus in the newborn has concommitant blocks at the level of the junction of the common canaliculus with the lacrimal sac and at the distal end of the nasolacrimal duct. This results in a typical pink or blue swelling in the region of the medial canthus. Spontaneous resolution is common, although dacryocystitis may supervene. Treatment should be conservative unless dacryocystitis occurs, or intranasal extension coexists. A series of seven co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Unilateral involvement has been reported to range from 60% 13 to 100%, 1,6,8,14 similar to the 89% reported in this cohort. Likewise, a large proportion of the study patients (89%) were non-Hispanic whites, as has been reported in prior studies (83% 3 to 100% 6 ). Three-fourths of the study patients were female, consistent with prior reports ranging from 20% 13 to 100%, 1 with the majority being above 57%.…”
Section: Discussionsupporting
confidence: 85%
“…Unilateral involvement has been reported to range from 60% 13 to 100%, 1,6,8,14 similar to the 89% reported in this cohort. Likewise, a large proportion of the study patients (89%) were non-Hispanic whites, as has been reported in prior studies (83% 3 to 100% 6 ). Three-fourths of the study patients were female, consistent with prior reports ranging from 20% 13 to 100%, 1 with the majority being above 57%.…”
Section: Discussionsupporting
confidence: 85%
“… 8 However, one may expect recurrence or infection in >20%. 9,13,14 Schnall and Christian described 17 patients who were treated conservatively with 76% resolving within 1 week. However, 4 of the 17 patients (24%) developed dacryocystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment is initially recommended (lacrimal sac massage, topical and/or systemic antibiotic therapy) during the first months of life. (23)(24)(25) Lacrimal probing is recommended when conservative treatment is ineffective or when the child presents severe infection or respiratory distress. (26,27) According to the literature, early probing can prevent infections and sequelae (tissue distortion in the inner canthus, induction of corneal astigmatism, and anisometropic amblyopia).…”
Section: Discussionmentioning
confidence: 99%